A qualitative investigation of exercising with MS and the impact on the spousal relationship. Issue 1 (December 2015) - Horton, Sean; MacDonald, Dany; Erickson, Karl; Dionigi, Rylee
Abstract Background Multiple Sclerosis is an autoimmune disease that affects more than 2.3 million people around the world. Symptoms are numerous and varied, often having a profound effect on activities of daily living. While for many years individuals with MS were told to avoid exercise for fear of worsening their symptoms, recent research has emphasized the multi-faceted benefits associated with regular physical activity. Given the strain that MS can put on family and interpersonal relationships, the intention of this study was to investigate the exercise experiences of individuals with MS and the extent to which these experiences affect, or are affected by, their spousal relationship. Methods In-depth qualitative interviews were conducted with 10 individuals, five with MS, along with each of their spouses, in order to gain a comprehensive understanding of living and exercising with the disease. An inductive approach was used to analyze the interview data. Results The results displayed the important physical, psychological, and social benefits of involvement in an exercise program. Spouses help to counteract barriers and facilitate exercise, and are well aware of the integral role they play in their partner's health and well-being. Spouses also valued the increased independence they gained, in the form of reduced care-giving responsibilities and enhanced social opportunities, as a result of the improved physical function of their partner. These findings contrast the severe strain on spousal relationships that is often reported in studies on people living with MS. Conclusions Rather than an inexorable downward decline in physical ability that is common with MS, participants spoke of a positive reversal in physical function, which has had far-reaching implications for multiple aspects of their lives, including their psychological outlook, their sense of independence, overcoming isolation, and their relationship with their spouse, all of which are identified in the literature as notable aspects of life affected by the disease.